Forecasting Customer Growth at PT PLN (Persero) ULP Lakawan Using Linear Regression - Ramanda Asyari; Ayi Oktra Maulana; Ikhlas; Adha Rizki; Muhammad Ridho (CIB Nusantara, 2025)
Electrical energy is a fundamental necessity for the population. PT PLN (Persero) ULP Lakawan is a state-owned enterprise mandated by the government to manage the national power supply. The rising public demand for electricity has led to a significant increase in the potential number of customers. Consequently, forecasting the number of customers for the year 2026 is essential as a basis for strategic planning and decision making to ensure an adequate and reliable electricity supply. This study utilizes historical customer data from 2016 to 2025 to capture trend of customer growth st PT PLN (Persero) ULP Lakawan. By employing a Simple Linear Regression analysis, conducted through both manual Excel calculations and data analytics tools, the study predicts that the number of customers in 2026 will reach 56,632. The model demonstrated high precision with a P-Value of 0. Furthermore, the analysis revealed a substantial impact with an R-Square value of 98.73% and an exceptionally strong correlation (Multiple R) of 0.99. This research indicates that the Simple Linear Regression method is highly accurate for predicting customer growth.